2015
DOI: 10.3748/wjg.v21.i6.2000
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of complex cholangiolithiasis following orthotopic liver transplantation with interventional radiology

Abstract: Bile duct stones are a serious and the third most common complication of the biliary system that can occur following liver transplantation. The incidence rate of bile duct stones after liver transplantation is 1.8%-18%. The management of biliary stones is usually performed with endoscopic techniques; however, the technique may prove to be challenging in the treatment of the intrahepatic bile duct stones. We herein report a case of a 40-year-old man with rare, complex bile duct stones that were successfully eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…This study indicated that bile leaks and bile stones comprise 82.4% of biliary complications following LT 11 . One study found that the incidence of bile duct stones following LDLT was 10%, while another reported an incidence range of 1.8%‐18% 12,13 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This study indicated that bile leaks and bile stones comprise 82.4% of biliary complications following LT 11 . One study found that the incidence of bile duct stones following LDLT was 10%, while another reported an incidence range of 1.8%‐18% 12,13 …”
Section: Discussionmentioning
confidence: 92%
“…The technique of percutaneous transhepatic management of biliary stones has been reported as successful in children in the non‐LT setting 26,27 . In the setting of LT, one case report concerning a 40‐year‐old man with complex bile stones in the intra‐ and extra‐hepatic bile tracts indicated that a percutaneous interventional approach was utilized successfully in extracting the stones, with no complications post‐procedure 13 …”
Section: Discussionmentioning
confidence: 99%
“…Пошкодження епітелію слизової оболонки жовчних проток, зумовлене аутоімунним дисбалансом, вірусною чи бактеріальною інфекцією, токсичними речовинами чи аномаліями розвитку, призводить до важких структурних змін печінки, обумовлюючи високу смертність [3]. Особливу увагу дослідники зосереджують на терапевтичному та хірургічному лікуванні патології жовчних проток (гострий та хронічний холангіт [4,5], гнійний холангіт і холєдохолітіаз [6][7][8][9][10][11], непрохідність жовчних проток [12]). Кількість оперативних втручань на жовчних протоках за останні 10 років зросла на 56 % (близько 4100 оперативних втручань у рік), при цьому післяопераційна летальність складає 2,1 % [13].…”
unclassified